HONORS TUTORIAL: AMERICANS WITH DISABILITIES - Schlesinger, Lynn (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This tutorial will focus on "Americans with Disabilities." In particular we will examine the development and content of the Americans with Disabilities Act (ADA) of 1990, and its subsequent implementation. That the ADA was signed reflects the growth of a disability rights movement that has grown stronger since the late 1970’s. Through an exploration of the process by which legislation is enacted, and the complications involved in enforcing civil rights legislation, you will gain a better understanding of politics, disability studies and social movements in our society. – You may not feel that the ADA, or anything related to disability, is relevant to you. However, those who do not have a disability may want to consider themselves as TABS – or Temporarily AbleBodied. It is probable that in your lifetime you will experience disability, whether permanently or temporarily. You may know someone who has a disability. In this tutorial we will compare our own everyday definitions of disability with those found in the ADA, and in writings by people with disabilities. We will examine closely the terms "accessibility" and "reasonable accommodation."